Experience Effects in Finance: Foundations, Applications, and Future Directions - Malmendier, Ulrike (Review of Finance, 2021)
Abstract This article establishes four key findings of the growing literature on experience effects in finance: (i) the long-lasting imprint of past experiences on beliefs and risk taking; (ii) recency effects; (iii) the domain-specificity of experience effects; and (iv) imperviousness to information that is not experience-based. I first discuss the neuroscientific foundations of experience-based learning and sketch a simple model of its role in the stock market based on Malmendier et al. (2020a, b). I then distill the empirical findings on experience effects in stock-market investment, trade dynamics, and international capital flows, highlighting these four key features. Finally, I contrast models of belief formation that rely on “learned information” with models accounting for the neuroscience evidence on synaptic tagging and memory formation, and provide directions for future research.